Stratification Effects on Estuarine Mixing: Comparative Analysis of the Danshui Estuary and a Thermal Discharge Outlet - Yaozhao Zhong; Hwa Chien (Journal of Marine Science and Engineering)
Estuaries serve as transitional zones between rivers and the ocean, and their mixed dynamic characteristics are crucial for the transport, transformation, and cycling of materials. This study investigates the mixing characteristics and their dominant factors in the Danshui Estuary and thermal discharge outlets through field measurements. Based on CTD (Conductance Temperature Depth) profiles and nutrient concentration measurements, the Danshui Estuary exhibited significant stratification during the October 2016 cruise, while vertical mixing was uniform during the March 2017 cruise. Vertical mixing was suppressed during stratification, but the nutrient concentration varied with salinity in a manner that was similar to non-stratified conditions, generally conforming to the theoretical dilution curve, which means physical mixing dominated here, indicating that horizontal mixing is predominant in the Danshui Estuary. The spatial scale calibrated horizontal dispersion coefficients were measured as 9.16 ± 1.57 m2 s−1 and 11.84 ± 1.71 m2 s−1 for stratified and non-stratified conditions, respectively, highlighting the Danshui Estuary’s strong horizontal mixing. Thermal discharge outlets are an important type of estuarine environment in non-natural estuaries. The 3D thermohaline structure measured by the underway CTD revealed an upwelling of cold and high-salinity water during the flood tide. The calculated Richardson number during the flood tide was approximately 0.7, indicating a very strong stratification effect. The horizontal dispersion coefficients calibrated by spatial scale showed no significant difference between different tides (flood tide: 0.53 ± 0.18 m2 s−1, ebb tide: 0.46 ± 0.17 m2 s−1). Therefore, the slower temperature decay during the flood tide, as reflected by the e-folding time (flood tide: 4.19 ± 2.33 min, ebb tide: 2.14 ± 0.40 min), is attributed to the strong stratification. Based on these findings, it is recommended that the power plant mitigates the impact of waste heat on the marine environment by increasing discharge during the ebb tide and reducing it during the flood tide.